Inversion Formulas for the Dunkl Intertwining Operator and Its Dual on Spaces of Functions and Distributions - Trimèche, K. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
In this paper we prove inversion formulas for the Dunkl intertwining operator Vk and for its dual tVk and we deduce the expression of the representing distributions of the inverse operators Vk⁻¹ and tVk⁻¹, and we give some applications.